Spiritual Experiences in Nature, Eco-Friendliness and Human Well-Being - Pater, C. de (Acta horticulturae, 2015)
The influence of spiritual experiences on the benefits of nature on health and well-being has been the subject of a small but increasing body of empirical research. This paper presents an overview of these studies and presents the author’s own research into the spiritual and other deep-felt values held by forest and nature managers. Analysis of respondents’ statements yielded three clusters of concepts: 1) the intra-personal process; 2) the relation between the manager and the forest; and 3) the relation between the manager and the transcendental. This paper discusses the interactions between these concepts and argues that the dynamics found in them can be interpreted as a ‘spiritual journey’, an iterative learning process with the spiritual experience as the ‘ultimate’ (though ephemeral) goal. This journey can be visualised in a lemniscatic form which combines empirical learning with intuitive learning, thus reconciling the outer and the inner world and generating meaning. The model is then applied to discuss benefits and pitfalls of the spiritual experience in nature. Benefits are mostly connected to spiritual growth generating psychic and physical health. Pitfalls can be identified when the two cycles are not fully completed, not balanced or separated altogether, the latter potentially leading to extreme forms of either materialism or immanentism. The challenge is to bring the balance back again, to be beneficial for the environment as well as for human well-being.